2020
DOI: 10.1111/vde.12911
|View full text |Cite
|
Sign up to set email alerts
|

Regional alopecia and dermatitis due to Lodderomyces elongisporus in a North American porcupine (Erethizon dorsatum)

Abstract: Background Lodderomyces elongisporus is a yeast with a worldwide distribution that has been reported as a cause of infection in immunocompromised humans and in a dog that had been quilled by a porcupine. Objectives The objective of this report is to describe the clinical presentation, diagnosis and treatment of dermatitis caused by L. elongisporus in a North American porcupine (Erethizon dorsatum). Animal One wild adult male North American porcupine from New York state, USA. Methods and materials The porcupine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Lodderomyces elongisporus is a fungus that has previously been identified as a cause of dermatitis in a North American porcupine and has been suggested to be part of the normal microbial skin flora in E. dorsatum . 34 Thick crusts often cracked and sometimes resulted in underlying skin laceration with contamination of underlying tissues. Additionally, thick perineal crusts often resulted in urine and fecal soiling and skin contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Lodderomyces elongisporus is a fungus that has previously been identified as a cause of dermatitis in a North American porcupine and has been suggested to be part of the normal microbial skin flora in E. dorsatum . 34 Thick crusts often cracked and sometimes resulted in underlying skin laceration with contamination of underlying tissues. Additionally, thick perineal crusts often resulted in urine and fecal soiling and skin contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a porcupine with alopecia and dermatitis caused by L . elongisporus [ 28 ]. These studies suggest that porcupines could be a potential reservoir and/or carrier of L .…”
Section: Potential Transmission Routes Of L ...mentioning
confidence: 99%
“…One report described a dog being quilled by a porcupine and subsequently developed pericarditis and endocarditis due to L. elongisporus infection [27]. Another study reported a porcupine with alopecia and dermatitis caused by L. elongisporus [28]. These studies suggest that porcupines could be a potential reservoir and/or carrier of L. elongisporus.…”
Section: Potential Transmission Routes Of L Elongisporusmentioning
confidence: 99%